(untitled) (Biological Sciences - PJSIR, 2022)
The experiment was conducted at Biochemistry Section, Ayub Agricultural Research Institute, Faisalabad Pakistan, during the year 2017-18 to assess the total phenols and antioxidants potential of mango, grapes, banana, guava, mulberry, strawberry, loquat, melon, apricot and phalsa. Fruits samples were obtained from the market of Faisalabad Pakistan, washed, dry at room temperature, extracted their juice/pulp. The juice was stored at 4 °C for further analysis. Juice samples were processed for Vitamin- C, pH, TSS, total phenolics and total antioxidant capacity. The results showed that among all the ten fruits vitamin C was higher in mango (24.33 mg/100 mL) followed by phalsa (19.74 mg/100 mL) and Grapes (11.25 mg/100 mL), whereas lower value was observed in melon (3.3 mg/100 mL) and loquat (3.4 mg/100 mL). Vitamin C for other fruits lies between these. Highly acidic pH of fresh juices of all the fruits was observed except in melon (5.82) and guava (5.38) which is less acidic. Percentage of TSS was higher in phalsa, mulberry and mangoes (13.8, 13.5 and 13.9% respectively) and lesser in melon (5.6%). Antioxidant capacity (% DPPH reduction) was found higher in grapes (91.9%) and mango (91.2%) which was statistically at par with melon (90.9%), while lesser value was observed in mulberry (51.6%). Total phenolics were significantly higher in grapes (1266.4 µg GAE/mL), whereas minimum phenolic contents were found in melon (4.1 µg GAE/mL). Therefore, it was concluded that grapes are more nutritious and healthy fruit than other.